2023
DOI: 10.3389/fpsyg.2023.1122339
|View full text |Cite
|
Sign up to set email alerts
|

Which type of fear of cancer progression contributes to the quality of life of Romanian cancer patients during the COVID-19 pandemic?

Abstract: IntroductionFear of cancer progression (FoP) is one of the most frequently reported unmet needs invoked by the majority of cancer patients, which may significantly impair the quality of life (QoL) of patients. The major objective of the present cross-sectional study was to investigate the specificities of the relationship between different dimensions and intensity of FoP and different aspects of patients’ QoL during the COVID-19 pandemic in Romania.MethodsA nationwide sample of 330 participants completed a sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Other Romanian-validated instruments that can be further used for assessing quality of life are the SF-36 (short-form health survey) [36], the EQ-5D-3L (EuroQOL-five dimensions, three levels), the 5L, 5D instrument [37,38], and KIDSCREEN-27 [39], which have been applied in several studies. In our review, we found 20 studies in Romania assessing distress, mental well-being, fear of progression, coping, irrational beliefs, and emotion thermometers [40][41][42][43]. Regarding Romanian cancer patients, the QLQ-C30 versions of the EORTC, FACT-B, and SF-36 were used to assess quality of life in five cross-sectional studies with a focus on breast cancer, laryngeal cancer, and other psychological variables [40,[44][45][46][47], as seen in Table 1.…”
Section: Psychological Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Romanian-validated instruments that can be further used for assessing quality of life are the SF-36 (short-form health survey) [36], the EQ-5D-3L (EuroQOL-five dimensions, three levels), the 5L, 5D instrument [37,38], and KIDSCREEN-27 [39], which have been applied in several studies. In our review, we found 20 studies in Romania assessing distress, mental well-being, fear of progression, coping, irrational beliefs, and emotion thermometers [40][41][42][43]. Regarding Romanian cancer patients, the QLQ-C30 versions of the EORTC, FACT-B, and SF-36 were used to assess quality of life in five cross-sectional studies with a focus on breast cancer, laryngeal cancer, and other psychological variables [40,[44][45][46][47], as seen in Table 1.…”
Section: Psychological Toolsmentioning
confidence: 99%
“…In our review, we found 20 studies in Romania assessing distress, mental well-being, fear of progression, coping, irrational beliefs, and emotion thermometers [40][41][42][43]. Regarding Romanian cancer patients, the QLQ-C30 versions of the EORTC, FACT-B, and SF-36 were used to assess quality of life in five cross-sectional studies with a focus on breast cancer, laryngeal cancer, and other psychological variables [40,[44][45][46][47], as seen in Table 1. Emotional distress and a catastrophizing coping strategy had a negative effect on the QoL.…”
Section: Psychological Toolsmentioning
confidence: 99%